The Influence of the Tanah Lot Art and Food Festival on Tourist’ Visiting Interest - Ni Kadek Intan Permata Putri Ni Kadek; I Nengah Wirata; Nyoman Reni Ariasri (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: This research aims to determine the influence of the Tanah Lot Art and Food Festival on tourists' interest in visiting Tanah Lot. Method: This research employs a quantitative approach at the Tanah Lot Tourist Attraction (DTW) in Beraban, Tabanan, over a five-month period (January - May 2024). Data was collected through questionnaires to examine the influence of the Tanah Lot Art and Food Festival on tourists' interest in visiting. Data analysis was conducted using simple linear regression with SPSS. Result: The results indicate that the Tanah Lot Art and Food Festival has a positive and significant impact on tourists' interest in visiting, both partially and simultaneously. Partially, the t-value (5.398) exceeds the t-table value (1.660), and the significance value (0.000) is less than 0.05. Simultaneously, the F-value (12.875) exceeds the F-table value (2.70), and the significance value (0.000) is less than 0.05. The festival contributes 35.2% to the tourists' interest in visiting, while 64.8% is influenced by other variables not examined in the study. Contribution: This research makes significant contributions in several areas. Theoretically, it enhances the literature on the impact of art and food festivals on tourist interest. Practically, the findings offer valuable insights to the management of Tanah Lot Tourist Attraction (DTW) and local government on strategies to boost tourist visits through event organization. Additionally, from a policy perspective, the empirical evidence provided can support the formulation of policies for the development and promotion of event-based tourism